Developing and expanding the Late-Glacial and Holocene tephrochronological framework of France: A new contribution from the Chaîne des Puys volcanic field in the Massif Central. (30th October 2022) - Jouannic, Gwénolé; Walter-Simonnet, Anne-Véronique; Bossuet, Gilles; Boivin, Pierre; Cubizolle, Hervé; Delabrousse, Eric; Develle, Anne-Lise; Devidal, Jean-Luc; Oberlin, Christine; Pigny, Béatrice
Abstract: The aim of this paper is to highlight new occurrences of tephra and cryptotephra layers from three peatbogs located southeastern from the French Massif Central in France. These tephras were evidenced using magnetic susceptibility logging, scanner imagery and chemical analyses by X-Ray Fluorescence, and characterized by their glass chemistry. Originated from the Chaîne des Puys volcanic field, these six new tephras allow for the definition of a more detailed regional tephrostratigraphic framework. Most of these tephras were deposited between ca. 13, 500 and 9500 yrs cal. BP, and the last one was deposited between 6400 and 5920 yrs cal. BP. Some tephras of this framework were previously described in the Jura Mountains, the Northern Alps and the Western Swiss Plateau, and allow its correlation to the Northern European context established by previous studies.